The sweet taste of muscadines : a novel - Terry, Pamela, 1956- (Ballantine Books, 2021)
"In this intimate debut novel, a woman returns to her small Southern hometown in the wake of her mother's sudden death--only to find the past upended by stunning family secrets. Lila Bruce Breedlove never quite felt at home in Wesleyan, Georgia, especially after her father's untimely death when she was a child. Both she and her brother, Henry, fled north after high school, establishing fulfilling lives and relationships of their own, steeped in art and culture. In contrast, their younger sister, Abigail, opted to remain in Georgia to dote on their domineering, larger-than-life mother, Geneva. Yet, despite their years-long independence, Lila and Henry both know they've never quite reckoned with their upbringing. Now, when their elderly mother dies suddenly and strangely in the muscadine arbor behind the family estate, they must travel back to the town that raised them. But as Lila and Henry uncover more about Geneva's death, shocking truths are revealed that upend the Bruces' history as they know it, sending the pair on an extraordinary journey to chase a truth that will dramatically alter the course of their lives. With deep compassion and sharp wit, Pamela Terry brings to life the culture and expectations of a small Southern town that values appearance over authenticity--and where the struggle to live honestly can lead to devastating consequences"--